2014
DOI: 10.1111/jfpp.12349
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Process and Antioxidant Activity of Polysaccharides from Leaves of A rtemisia argyi  Levl. et Vant

Abstract: Box–Behnken design including independent variables such as extraction temperature (80–100C, X1), extraction time (1.5–2.5 h, X2) and ratio of water to raw material (15–25 mL/g, X3) was employed to optimize the extraction of polysaccharides from the leaves of Artemisia argyi (AAP). The optimized extraction parameters were as follows: extraction temperature of 100C, extraction time of 2.27 h and ratio of water to raw material of 21.5 mL/g. The experiment extraction yield of AAP was 2.15 ± 0.09% under the optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The ABTS radical scavenging activity of Artp2 (10 mg/mL) reached 76.19%, indicating the efficient antioxidant activity ofArtp2. This result is similar with the previous study, which indicated that a polysaccharide extracted from A. argyi displayed good ABTS radicals scavenging effects [ 27 ]. However, Artp2 showed significantly higher ABTS scavenging activity (76.19%) than that of Artp1 (19.64%) at 10 mg/mL, which might also be due to the fact that Artp2 contains a higher amount of phenolic, protein, and uronic acid.…”
Section: Resultssupporting
confidence: 93%
“…The ABTS radical scavenging activity of Artp2 (10 mg/mL) reached 76.19%, indicating the efficient antioxidant activity ofArtp2. This result is similar with the previous study, which indicated that a polysaccharide extracted from A. argyi displayed good ABTS radicals scavenging effects [ 27 ]. However, Artp2 showed significantly higher ABTS scavenging activity (76.19%) than that of Artp1 (19.64%) at 10 mg/mL, which might also be due to the fact that Artp2 contains a higher amount of phenolic, protein, and uronic acid.…”
Section: Resultssupporting
confidence: 93%
“…[5][6][7] Furthermore, polysaccharides were recently extracted from Artemisia argyi and their immunomodulatory activity and antioxidant activity were conrmed. 8,9 Moreover, growing evidences have indicated that polysaccharide has prebiotic potential through altering the composition and abundance of benecial gut microbiota. It has shown that the gut microbiota plays a critical role in nutrient uptake, utilization, and metabolism, which may contribute to metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitated pellet was washed with different percentages of ethanol to remove soluble material and deproteinized using sevag method (Zou, Jiang, & Tian, 2015). A brown coloured crude polysaccharide was obtained (C.-L. Ye & Lai, 2015) and the concentration was determined by using Phenol-Sulphuric acid method (DuBois, Gilles, Hamilton, Rebers, & Smith, 1956). The yield was calculated using the following equation: …”
Section: Methodsmentioning
confidence: 99%